Adequacy of DEA in Measuring the Efficiency of Public Sector Entities in Nigeria: A Comparative Analysis Approach - Olawale, Odewole, Philip (Journal of Economics and Behavioral Studies, 2020)
The study examined the efficiency of Decision- Making Units (DMUs) in the public sector entities in Nigeria. The study focused on the efficiency in the utilization of personnel cost releases to the federal educational and health institutions by the Federal Government of Nigeria. Secondary data were sourced from the Annual General Warrants from Audited financial statements of the Public Sector entities. Sampled size for the study comprised twenty-five (25) DMUs each from both sectors out of the major Federal Ministries from four (4) geo-political Zones and Abuja. Data were analyzed using Data Envelopment Analysis Model (DEA). The results of the average efficiency scores from both Charnes, Cooper and Rhodes Model (CCR) and Banker, Charnes and Cooper (BCC) on the DMUs showed that the sectors were marginally inefficient. The summary of the overall results therefore revealed that the DMUs under health sector performed averagely better than education sector in the utilization of personnel cost allocations. The study recommended that a central monitoring team be created jointly by the Federal Ministry of Finance and Accountant-General’s office to ensure full utilization of personnel cost releases to the DMUs. The study therefore concluded that only continuous assessment and periodic appraisal of the personnel cost utilization by the supervising ministries, can guarantee full efficiency in the utilization of personnel cost releases.